The Development Of Smoked Selais Fish As A Gastronomic Tourist Attraction In Riau Province - Thamrin, Syahrul (Universitas Pendidikan Indonesia, 2020)
Kryptopterus lais or commonly known as selais fish is one of the unique faunas of Riau Province. Selais Fish even made as an icon of Riau Province. The icon is exhibited right at the Pekanbaru Mayor's Office on Jalan Jendral Sudirman, tourists can find it in the form of a monument selais fish. The monument was named Selais Tiga Sepadan. The development of selais fish as a tourist attraction is supported by traditional fish management. It advances economic value and attracting tourists in unique ways such as catching fish with a traditional tool called bubu, and enjoying the views of swamp forest using traditional boats during the tours in Riau. Excessive exploitation and land clearing in the area of Dumai results in a decline and soaring in selais fish prices. Selais fish income from year to year has decreased. This research uses qualitative research methods, the sampling of sources and data is done purposively. The data collection technique is done by inductive triangulation of data analysis, and the results of qualitative research emphasize more on meaning than generalization. In addition, it appears necessary to add types of fish that are salted / smoked as food choices made by tourists and improve the packagingâ€™s attractiveness. The development of smoked salais fish as a tourist attraction for gastronomic can increase the economic competitiveness with other regions. This research, discovered that selais fish as Malay special food increases tourist visits for its delicious meat, attractive tourism packages and good management.Â